Mucinous cystic neoplasm of the liver: a case report. Issue 7 (23rd July 2020) - Yeh, John; Palamuthusingam, Pranavan
Abstract: A 50-year-old woman was investigated for epigastric pain. Imaging revealed a multilocular cyst with multiple thin septae within segment IV of the liver, measuring up to 140 mm in diameter. There was associated bile duct dilatation. Given the patient's symptoms, the size of the cyst and malignant potential, a hemi-hepatectomy was performed. Histopathology demonstrated a cyst lined by columnar mucinous epithelium with underlying ovarian-type stroma. Therefore, the diagnosis was mucinous cystic neoplasm of the liver (MCN-L). MCN-L is a rare disease, and the presence of bile duct dilatation is an even rarer finding. This article presents a case report and review of literature of this entity.